INFLUENCE OF INITIAL pH SOLUTION ON BIOFILM FORMATION AND CORROSION OF CARBON STEEL BY Serratia marcescens - Ardiyan Harimawan; Hary Devianto; Ignatius Chandra Kurniawan; Josephine Christine Utomo (Reaktor, 2017)
The growth of Serratia marcescens depends on its metabolism, which is influenced by environmental factors, such as pH and temperature. The metabolic activity of Serratia marcescens may influence the corrosion of carbon steel by forming a biofilm on the metal surface. This research is focused on determining the effect of pH on carbon steel corrosion caused by Serratia marcescens. The medium used as immersion solution was a mixture of synthetic seawater and Luria-Bertani medium with a volume ratio of 4:1. The carbon steel coupons with a size of 1 cm x 1 cm were immersed in the solution with initial pH of 5, 7, and 9. The analyses of biofilm were conducted by total plate count (TPC), scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR). Biofilm was detected evenly on the metal surface and decreased with an increase in incubation pH. The biofilm consists of some functional groups, such as alcohol, alkane, amine, nitro, sulphate, carboxylic acid, and polysulfide. The analyses of the corrosion were conducted by gravimetric and X-ray diffraction (XRD). The pHs of 5 and 9 were found to give an increase in the corrosion rate. The average corrosion rate at pH variations of 5, 7, and 9 were 2.5309 g/m2.day; 2.2844 g/m2.day; and 2.9756 g/m2.day, respectively. Nevertheless, the corrosion products were not detected by XRD analysis. Keywords: biocorrosion; carbon steel; pH; seawater; Serratia marcescens   Abstrak PENGARUH pH AWAL LARUTAN PADA PEMBENTUKAN BIOFILM DAN KOROSI BAJA KARBON OLEH Serratia marcescens. Laju pertumbuhan Serratia marcescens bergantung pada aktivitas metabolise mikroba, yang akan sangat dipengaruhi oleh faktor lingkungan, seperti pH dan temperatur. Aktivitas metabolisme Serratia marcescens dapat memengaruhi korosi pada baja karbon dengan membentuk lapisan biofilm pada permukaan logam. Penelitian ini bertujuan untuk menentukan efek pH pada korosi baja karbon yang disebabkan oleh Serratia marcescens. Media yang digunakan sebagai larutan perendam adalah campuran air laut sintetis dan media Luria-Bertani dengan perbandingan volume sebesar 4:1. Kupon baja karbon dengan ukuran 1 cm x 1 cm direndam dalam larutan dengan pH awal 5, 7, dan 9. Analisis lapisan biofilm dilakukan dengan total plate count (TPC), scanning electron microscopy (SEM) dan Fourier transform infrared spectroscopy (FTIR). Lapisan biofilm tumbuh secara merata pada permukaan logam dan berkurang seiring dengan peningkatan pH inkubasi. Lapisan biofilm mengandung berbagai gugus fungsional, seperti alkohol, alkana, amin, nitro, sulfat, asam karboksilat, dan polisulfida. Analisa korosi dilakukan dengan gravimetri dan X-ray diffraction (XRD). Penggunaan pH 5 dan 9 memberikan peningkatan terhadap laju korosi. Laju korosi rata-rata pada pH 5, 7, dan 9 ditentukan sebesar 2,5309 g/m2.day; 2,2844 g/m2.day; and 2,9756 g/m2.day. Namun, produk korosi tidak terdeksi oleh analisis XRD. Kata kunci: biokorosi; baja karbon; pH; air laut; Serratia marcescens